The Codicological Analysis Of The Work "Al-Jawharat Al-Nayyira" - Qosim Abdullo Mirabzal o’g’li (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article provides a codicological analysis of the work "Al-Jawharat al-Nayyira" by Abu Bakr Haddad, which is one of the reputable fiqh sources of the Hanafi madhhab. The analysis covers the manuscript and printed versions of the work, as well as its modern editions.